Relationship between nocturia and hypertension: findings from the NHANES 2005–2016 - Chen, Junhao; Liu, Zhenghuan; Yang, Luchen; Zhou, Jing; Ma, Kai; Peng, Zhufeng; Dong, Qiang (Frontiers in Cardiovascular Medicine, 2023)
Objectives: The objective of this study was to explore the association between nocturia and hypertension in a large, nationally representative adult sample. Methods: We used data from 2005-2016 National Health and Nutritional Examination Surveys (NHANES). A total of 29505 participants aged 20 years old or older were included. A participant was considered to have nocturia if he or she had two or more voiding episodes at night. Multivariable logistic regression models were used to explore the association between nocturia and hypertension. Results: Participants with nocturia were associated with a higher risk of hypertension (OR 1.36; 95% CI 1.28-1.45). Interaction tests revealed no significant effect of sex, age, race, or body mass index on the association of nocturia with hypertension. As the severity of nocturia increases, the risk of hypertension increases (P for trend <0.0001). In addition, nocturia was also related to different grades of hypertension (II vs I: OR 1.34, 95% CI 1.16-1.55; III vs I: OR 1.67, 95% CI 1.32-2.13). Conclusion: In this cross-sectional study, our results suggest that nocturia is associated with an increased risk for hypertension.